Theory of world politics - Albert, Mathias (Cambridge Cambridge University Press, 2016)
"In this book, Mathias Albert develops an ambitious theoretical framework that describes world politics as a specific social system set within the wider political system of world society. Albert's analysis of the historical evolution and contemporary form of world politics takes the theory of social differentiation as its starting point. World politics is a specific, relatively recent form of politics and Albert shows how the development of a distinct system of world politics first began during the long nineteenth century. The book goes on to identify the different forms of social differentiation that underlie the variety of contemporary forms of organizing political authority in world politics. Employing sociological and historical perspectives, A Theory of World Politics also reflects critically on its relation to accounts of world politics in the field of international relations and will appeal to a wide readership in a range of fields"--
"The present book proposes a theory of world politics. It analyses world politics as a specific and historically relatively recent form of politics. It takes politics to be a functionally differentiated realm of modern society, and it takes modern society to be a world society. Put more formally in terms of an approach based on systems theory: world politics is a subsystem of the (functionally differentiated) political system of world society. This book is about world politics. It is not an international relations book, nor is it a sociology book - nor, for that matter, is it a history book. It is a book arguing that to understand world politics as a social system within world society requires pooling the fund of knowledge of all of these disciplines. Such a design will, hopefully, lead to a range of insights and make for a stimulating read. However, it does provide a challenge to those more immersed in specific, discipline-focused approaches to the subject"--
Machine generated contents note: Introduction; Part I. World Society Theory: 1. The 'world' and 'society' in 'world society'; 2. World society and social differentiation: segmentation, stratification, and functional differentiation; Part II. Emerging World Politics: 3. The system of world politics; 4. Forms of world politics; Part III. Reflections and Roads Ahead: 5. Reflections on theorising world politics; 6. Limitations, loose threads, further research; Concluding remarks: scrambles amongst world politics.
Includes bibliographical references and index.
Keywords: International relations -- Philosophy; International organization -- Philosophy; Differentiation (Sociology)